Pendampingan Penyusunan Laporan Keuangan Bakpia Yasmin Sesuai Dengan Standar EMKM - Mukti Prasaja; Rika Alfiana; Tera Salsabila; Emilya Saputri (JCSE: Journal of Community Service and Empowerment, 2025)
Indonesia's current economic growth as a support for development development, one of which is Micro, Small and Medium Enterprises (MSMEs). This is shown by the number of business actors and the high absorption of labor for MSMEs by 97%. Bakpia Yasmin's business is one of the MSMEs engaged in the food sector. Bakpia Yasmin was founded by Mrs. Yusmini since 2020 which is located in Mojorayung Village RT 16/RW 04, Wungu District, Madiun Regency, East Java. Based on the results of the interview. The recording includes the total orders for the day as well as offline and online on a small whiteboard that is updated every day. Furthermore, it is also recorded on a piece of paper without a book which has not been properly archived. Therefore, from these problems, assistance has been carried out in the preparation of financial statements based on EMKM standards for Bakpia Yasmin MSMEs. The participants were very enthusiastic in participating in this training, and hopefully they can use financial statements as evaluation materials for the business carried out